Improvement of material modeling by considering the plane strain and shear stress state in the Yld2000-2d yield criterion - Rentz, Marcel; Merklein, Marion (Journal of Physics: Conference Series, 2025)
Precise material modeling is an important factor in improving the mapping accuracy of a sheet metal forming process in the simulation. Many conventional material models, such as Hill'48 or Yld2000-2d, do not consider the plane strain and shear stress state, even though these conditions are responsible for a significant proportion of material failure during deep-drawing. These two states are only approximated based on the input data. Hence, the approach of the present work is to adapt the existing material model Yld2000-2d by varying the yield locus exponent. As a consequence, it is possible to accurately map the real material behavior under plane strain or shear. Therefore, shear tests and hydraulic bulge tests with elliptical die are carried out to characterize the principal stress components under the mentioned stress states. The improvement of the mapping accuracy using the new adapted material models is evaluated by comparing the sheet thickness distribution of numerically calculated and experimentally deep-drawn cross-die specimens. Two different materials DC06 and AA5182 are being investigated. For both materials it can be shown that a reduction of the yield locus exponent leads to a better mapping of the plane strain state, while higher yield locus exponents are better suited to describe the material behavior under shear.
CRIS-Team Scopus Importer:2025-10-31